Reception antennas for low orbit earth satellites - Ciafardini, Juan Pablo (2011)
This paper describes the design and construction of antennas for the detection of low orbit satellites, and in particular NOAA (National Oceanic and Atmospheric Administration) meteorological satellites. Based on an analysis of the requirements needed to detect signals from weather satellites, the design and simulation of antennas is made. The simulations allowed to analyze the electromagnetic processes and evaluate the radiation patterns and polarization characteristics of the designed antennas. Using the commercial software FEKO Suite 6.0 the dimensions of the antennas were optimized and the requirements checked. Selected designs were compared with references of works done on the subject. In order to validate the design, the antennas were built and measurements were made to verify the design parameters.